Dynamics of Foreign Direct Investment in Rajasthan - Pawan Kumar (Global Journal of Human-Social Science, 2024)
Rajasthan a land of promises has received 1549 10 crore FDI inflows in 2019-20 and 6259 48 crore in 2022-23 which is about a 304 per cent increase in FDI inflows in the last four years FDI inflows have grown at a Compound Annual Growth Rate CAGR of 33 23 percent in Rajasthan in the post-liberalization period in India While the states are competing to attract more FDI inflows organize investor s summit and initiate policy reforms to facilitate investment opportunities in their region This study aims to analyse determinants of FDI inflow in Rajasthan state which is a landlocked state with an abundance of natural resources and skilled manpower Foreign Direct Investment FDI a nondebt- creating capital inflow stimulates employment generation and fills the gap between domestic saving and investment It is found that there is a direct relation between FDI inflows and the Gross Domestic Product growth of the host state It is a global phenomenon that FDI inflows create inter and intra-regional imbalances Statically Rajasthan falls in laggard states in terms of receiving FDI inflows which receive about 1 percent of the total FDI inflows of the country However Rajasthan receives the maximum FDI inflow share among the BIMARU states of India This study attempts to investigate determinants of FDI in the state highlights the bright opportunities and potential of the state to attract quite more FDI in sectors like Automobile tourism Metallurgical Logistics and Food processing industry Secondary data is obtained from Department for promotion of industries and internal trade DIPIIT Reserve bank of India RBI publications and The Directorate of Economics and Statistics DES using linear regression analysis on time series data Though it is elusive to find determinants of FDI inflow However this study reveals that there is a strong correlation between FDI SGDP Infrastructure and availability of credit and Net value Added by the industrial sector of the region